ANALISIS KEKUATAN IMPACT KOMPOSIT POLYESTER BERPENGUAT SERBUK KAYU JATI DENGAN VARIASI FRAKSI VOLUME MATRIKS DAN REINFORCEMENT - Ariantika, Kadek; Wiratmaja, I Gede; Nugraha, I Nyoman Pasek (Universitas Negeri Surabaya, 2024)
The biggest problem facing the automotive industry today is limited natural resources and environmental protection. Therefore, it is very important to conduct and carry out research and mapping of alternative materials that can reduce the use of non-renewable materials. The aim of this research is to determine the effect of variations in the volume of teak wood powder on the impact strength of composites with a polyester polymer matrix and identify fracture patterns. This research uses an experimental design combined with one-way statistical analysis of variance to test the research hypothesis. The results showed that there were significant differences in impact strength between the variations of the three specimens tested. Specimens with variations in volume fraction of 20%:80% for teak wood powder and polyester resin have the highest impact strength, while specimens with variations in volume fraction of 30%:70% for teak wood powder and polyester resin have the lowest impact strength. Apart from that, examination of the microscopic structure of the fracture patterns shows differences in fracture patterns between specimens. Specimens with variations in volume fraction of 0% (100% polyester resin) show a brittle fracture mechanism, while specimens of 10%:90%, 20%:80%, 30%:70% for teak wood powder and polyester resin show that the fracture pattern that appears is a combination of fragility and fibular fracture which is also called a fibrous fracture.